Molecular characterization, transcriptional profiling, and antibacterial potential of G-type lysozyme from seahorse (Hippocampus abdominalis). (November 2016) - Ko, Jiyeon; Wan, Qiang; Bathige, S.D.N.K.; Lee, Jehee
Abstract: Lysozymes are a family of enzymes that catalyze the hydrolysis of bacterial cell wall, acting as antimicrobial effectors of the innate immune system. In the present study, an ortholog of goose-type lysozyme (ShLysG) from the big-belly seahorse ( Hippocampus abdominalis ) was identified and characterized structurally and functionally. The full-length cDNA sequence (1213 bp) of ShLysG is comprised of an open reading frame made up of 552 bp, encoding a polypeptide of 184 amino acid (aa) with a predicted molecular mass of 20 kDa. In silico analysis of ShLysG revealed the absence of signal peptide and the presence of a characteristic bacterial soluble lytic transglycosylase (SLT) domain bearing three catalytic residues (Glu 71, Asp 84, and Asp 95 ) and seven N -acetyl-d -glucosamine binding sites (Glu 71, Asp 95, Tyr 98, His 99, Ile 117, Tyr 145, and Asn 146 ). Homology analysis demonstrated that the aa sequence of ShLysG shared 60.7–67.4% identity and 72.6–79.3% similarity with the orthologs of other teleosts. Phylogenetic analysis of ShLysG indicated a closest relationship with the ortholog from Gadus morhua . In healthy seahorse, ShLysG mRNA showed a constitutive expression in all the tissues examined, with the highest expression in kidney and the least expression in liver. The ShLysG mRNA levels were also shown significant elevation upon the bacterial and pathogen-associated molecular pattern (PAMPs) challenges. Furthermore, lytic activities of ShLysG recombinant protein were detected against several Gram-negative and Gram-positive bacterial species. Taken together, these results suggest that ShLysG might possess a potential immune defensive role against invading microbial pathogens in seahorse. Highlights: A goose-type lysozyme ( ShLysG ) from Hippocampus abdominalis was cloned. Expressional analysis of ShLysG after PAMPs and live pathogen infections was performed. Optimal conditions (pH and temperature) for lytic activity of (r)ShLysG were determined. Bactereolytic activity of ShLysG was examined using different strains.